1997
DOI: 10.1046/j.1365-2133.1997.6581643.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-BP180 autoantibodies as a marker of poor prognosis in bullous pemphigoid: a cohort analysis of 94 elderly patients

Abstract: The prognosis of bullous pemphigoid (BP), a disorder which usually affects elderly patients, is not well established and conflicting data have been reported about the mortality rate of the disease. Our objective in this study was to assess the clinical and immunological factors determining survival in a prospective series of 94 patients with BP. A cohort of 94 consecutive patients with BP (mean age +/- SD: 81 +/- 4 years) was studied over an 8-year period (1987-94) in one department and patients followed up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 18 publications
3
46
3
2
Order By: Relevance
“…Only one previous study provided evidence suggesting that presence of autoantibodies to BP180 by immunoblotting represented a poor prognostic factor [18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one previous study provided evidence suggesting that presence of autoantibodies to BP180 by immunoblotting represented a poor prognostic factor [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The first-year mortality rate varies between 10 and 44%, with significant differences between Europe and the USA [12,16,17]. Previous studies have identified a number of negative prognostic factors, such as age, low Karnofsky performance score and use of corticosteroids [16,18,19]. Immunosuppressive agents, systematic use of which has not been validated, may also affect the mortality rate [20].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The mortality of patients with BP in Europe, generally derived from larger studies, have been markedly higher, with 1-year mortality ranging from 19% to as high as 41%. [7][8][9][10][11][12][13][14] The reason for the large discrepancy in European versus US studies is unclear.…”
mentioning
confidence: 99%
“…Anti-BP180 antibodies detected by immunoblotting were found to be associated with death in the first year [16]. The role of ELISA-BP180 test for predicting relapse during the first year of treatment [17] or after treatment cessation was previously described, and a threshold of 27 UA/ml was found to be associated with relapse at 12 months after treatment cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The test is sensitive and specific (>90%) at the time of diagnosis [13,14] and results parallel the clinical activity of BP during treatment [15,16,17,18]. Values ≥27 arbitrary units (AU)/ml (3 times the 9 AU/ml threshold of the MESACUP BP180 and BP230 kit [MBL, Nagoya, Japan]) represent a major prognostic factor for predicting relapse after treatment cessation similar to persistent positive direct immunofluorescence (DIF) [6].…”
Section: Introductionmentioning
confidence: 99%